PENGARUH LATIHAN RESISTANCE BAND TERHADAP PENINGKATAN JUMPING SMASH DI KLUB BOLA VOLI LAMPUNG PHINISI - Anila Herdiana Putri; Reza Adhi Nugroho (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to determine whether resistance band training affects the improvement of jumping smash at the Lampung Phinisi Volleyball Club. The population of all students Participants in this study were members of the Lampung Phinisi volleyball club, while the sample of this study consisted of 20 Lampung Phinisi volleyball athletes. The training was carried out for a month with sixteen meetings, various exercises, and basic volleyball methods to avoid boredom. Based on the results of the study, the researcher obtained P is The calculated t value is 10.667, which is greater than the t table value, and 0.000, which is smaller than α (0.05) of 1.729). Based on these findings, the calculated t value is higher than the t table value, the significance value is less than 0.05, and the average increase is 6.1 feet. Therefore, the research findings show that resistance band training significantly improves jumping smash in Lampung Phinisi Volleyball Club, with an average increase from 241.95 feet before treatment to 248.05 feet after treatment, indicating 0.000 < 0.05 is the level of significance.